1991
DOI: 10.1007/bf00201539
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of medium-chain acyl-CoA dehydrogenase (MCAD) deficiency: identification of a lys329 to glu mutation in the MCAD gene, and expression of inactive mutant enzyme protein in E. coli

Abstract: Summary. A series of experiments has established the molecular defect in the medium-chain acyl-coenzyme A (CoA) dehydrogenase (MCAD) gene in a family with MCAD deficiency. Demonstration of intra-mitochon drial mature MCAD indistinguishable in size (42.5-kDa) from control MCAD, and of mRNA with the correct size of 2.4 kb, indicated a point-mutation in the coding region of the MCAD gene to be disease-causing. Con sequently, cloning and DNA sequencing of polymerase chain reaction (PCR) amplified complementary DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 22 publications
3
36
0
Order By: Relevance
“…Plasmids-The previously used plasmid pBMCK2- (8), which carries a gene encoding the mature part of human MCAD preceded by an artificial initiator methionine under control of the lac promoter, was modified in order to allow straightforward subcloning ofPCR amplified MCAD cDNA derived from patient material. For this purpose pB-MCK2-was modified in aseries of steps involving standard PCR and cloning techniques in the following way.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmids-The previously used plasmid pBMCK2- (8), which carries a gene encoding the mature part of human MCAD preceded by an artificial initiator methionine under control of the lac promoter, was modified in order to allow straightforward subcloning ofPCR amplified MCAD cDNA derived from patient material. For this purpose pB-MCK2-was modified in aseries of steps involving standard PCR and cloning techniques in the following way.…”
Section: Methodsmentioning
confidence: 99%
“…Besides aseries of rare point mutations, short insertions, and deletions (5-7), one prevalent point mutation (8)(9)(10)(11) is present in more than 90% ofthe alleles in patients with MCAD deficiency (5). This mutation is an A~G transition at position 985 of the cDNA sequence (G985), leading to replacement of lysine 304 in the mature protein with glutamic acid (K304E).…”
mentioning
confidence: 99%
“…MCAD deficiency is an autosomal length specific enzymes which catalyze the first step in recessive genetic disease which, in the majority of cases mitochondrial l3-oxidation of straight-chain fatty acids (approx. 90% of the alleles, [4]), is due to a point mutation at position 985 of the cDNA sequence [5][6][7][8] causing a lysine to glutamic acid exchange at position correctly [9]. We have shown that, unlike the wild formation of insoluble aggregates [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…90% of the alleles, [4]), is due to a point mutation at position 985 of the cDNA sequence [5][6][7][8] causing a lysine to glutamic acid exchange at position correctly [9]. We have shown that, unlike the wild formation of insoluble aggregates [5,10]. Upon overex pression in COS-7 cells, the K304E mutant has been demonstrated to be unstable and only very small amounts of tetrameric mutant MCAD could be detected [11].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately, 80% of these patients were homozygous for this mutation, and 18% were heterozygous for c.985A.G. 7,[58][59][60][61][62][63] In order to explore the founder effect hypothesis, Leal et al in 2014 combined genotyping and screening data from 43 publications reporting the frequency of c.985A.G spanning over 10 million individuals, and they found significant variation in the frequency of the mutation across regions supporting a reported founder effect. 58 The proportion Prior to NBS, the incidence of MCAD deficiency was approximately in the range 1 in 30,000 to 1 in 135,000.…”
Section: Molecular Aspectsmentioning
confidence: 99%